PRINSIP DASAR DAN RAGAM PENAFSIRAN KONTEKSTUAL DALAM KAJIAN AL-QUR’AN - Fauzul Iman (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2016)
With the caracteristic which is so-called “shâlih li kulli makan wa zaman” (suitable in all places and epoches), Qur’anic verses should be comprehended according to the different context of the society. The Qur’an should be able to answer everlasting different problems in different society. This is to make the Qur’ân that had been revealed fourteen centuries ago still alive and suitable for our era. This in turn inspires the rise of the context-oriented exegesis: a kind of exegesis which projects the past into the contemporary context. Apart from any shortcomings, contextual exegesis deserves appreciations and can can be a trend in Qur’anic exegesis which is in need to be developed. This article deals with basic principles and models of contextual exegesis in the study of al-Qur’an.